Exploring the Impact of ABO Blood Groups on BKV, CMV, and EBV Nephropathy Among Haemodialysis Patients in Erbil City: A Cross-Sectional Analysis - Kamil Abdulla, Abdulla; Abdulqader Al-Naqshbandi, Ahmed; Faruq Sadiq Zamzamokey, Faisal (American Journal of Biology and Natural Sciences, 2025)
Patients who have had an ABO-incompatible kidney transplant have a higher risk of contracting BKV infection. Patients on hemodialysis are still at serious risk for contracting Cytomegalovirus (CMV) infection. Patients who are immunocompromised, including those receiving hemodialysis, are at serious risk from Epstein-Barr virus (EBV). The current study aims at examine the connection between blood group and BKV, CMV, and EBV viral cases and controls. This cross-sectional study was conducted in Erbil City, Kurdistan Region, Iraq, utilizing data that was routinely collected at the central laboratory and at the level of tertiary care centers. The investigation took place between November 1, 2024, and January 30, 2025. Hundred twenty hemodialysis patients and 120 control group members participated. Information included gender, Age, Blood group, BKV, CMV, and EBV viral infection as determined by PCR and ELISA (IgM and IgG) were taken out electronically from medical records and laboratory databases at tertiary care centres and the central laboratory/Erbil, Iraq. The age distributions of the hemodialysis patients and the control group did not appear to differ significantly (P>0.05). No significant differences (P>0.05) in gender distribution were observed. Significant differences between the control group and the hemodialysis group were found in the frequency of ABO blood groups and Rh factor. Significant variations (P<0.05) in the distribution of Rh factor and ABO blood groups between hemodialysis patients infected with Cytomegalovirus (CMV) and control groups, this was also applicable to EBV. Significant differences (P <0.05) in the frequency of ABO blood groups with Rh factor among hemodialysis patients with BK virus (BKV) infection. Male participants with blood group O are more susceptible to haemodialysis. Patients with Cytomegalovirus positive are mostly have blood groups O positive A +ve and B +ve. Patients who were A+ve were more susceptible to get BK and EBV.